Genotoxicity of inhalational anesthetics and its relationship with the polymorphisms of GSTT1, GSTM1, and GSTP1 genes - Kargar Shouroki, Fatemeh; Neghab, Masoud; Mozdarani, Hossein; Alipour, Hamzeh; Yousefinejad, Saeed; Fardid, Reza (Environmental science and pollution research international, 2019)
Due to their wide applications, concern exists regarding possible genotoxic effects of inhalational anesthetics (IAs) among operating room personnel. This study was undertaken to examine genotoxic properties of co-exposure to nitrous oxide, sevoflurane, and isoflurane on induction of micronucleus (MN) and chromosomal aberrations (CAs) and to determine whether any associations exist between polymorphisms of GST genes and the level of genomic damage measured by MN and CAs assays. Sixty operating room personnel and 60 unexposed referent nurses were studied. The workers’ exposure to the IAs was determined. DNA damage was evaluated by MN and CAs assays. Additionally, the GSTM1 , GSTT1 , and GSTP1 polymorphisms were detected. The mean concentrations of nitrous oxide, isoflurane, and sevoflurane were found to be 850.92 ± 919.78, 2.40 ± 0.86, and 0.18 ± 0.14 ppm, respectively. The frequency of MN and CAs in the exposed group was significantly higher than that of the non-exposed group. The frequency of MN was significantly higher in referent nurses with null GSTT1 , compared to referent nurses with positive GSTT1 . The frequency of MN was significantly higher in exposed individuals carrying the combined genotype of GSTT1 (−), GSTM1 (−), and GSTP1 AG as compared with subjects carrying a combination of GSTT1 (+), GSTM1 (+), and GSTP1 AA . Statistically significant associations were noted between exposure to the IAs, gender, and the combination of the three GSTs genotypes with MN frequency. These findings indicate that inhalation exposure to IAs induces genotoxic response and the polymorphisms of GSTs genes might modulate the effect of exposure to IAs on MN.